Effects of Tanacetum parthenium on Chromatin Quality, Sperm Parameters and Oxidative Stress in Mice - Shabnam Mohammadi; Farimah Beheshti; Abbas Mohammadipour (Mazandaran University of Medical Sciences, 2024)
Background: Studies indicate that phytoestrogens and phytosterols have adverse effects on the male reproductive system. To our knowledge, the effects of Tanacetum parthenium on testicular tissue, spermatozoa chromatin integrity and free radical damage have not yet been investigated. Therefore, this study aimed to evaluate the effect of T. parthenium administration on sperm parameters, testis histology, sperm DNA integrity and oxidative damage in adult male mice.  Methods: Eighteen adult male mice (2-3 months old) were randomly divided into 3 groups: control, TP1 and TP2. TP1 and TP2 groups were separately gavaged with 50 and 100 mg/kg T. parthenium. After harvesting the epididymis, sperm analysis was performed according to the guidelines of the World Health Organization (WHO). The testicular tissue also passaged through the tissue routine process after being placed in a formalin fixative solution. To check the quality of sperm chromatin, a sperm smear was prepared and then stained with acridine orange dye and was examined with a fluorescent microscope. Biochemical parameters, including malondialdehyde (MDA), thiol, catalase enzyme, and superoxide dismutase (SOD), were measured in testicular tissue. Finally, data were analyzed by the analysis of variance in SPSS software, version 16.  Results: A significant reduction was seen in sperm count and sperm morphology percentage and the germinal epithelium thickness in the TP1 and TP2 groups versus the control group. The spermatozoa with DNA damage in percentage were higher in the TP1 group (21.22±3.70) and TP2 group (42.60±3.73) compared to the control group (2.40±4.3). There were remarkable differences between the three groups in MDA (P≤0.001) and thiol (P≤0.001) levels. Catalase level (P≤0.001) was lower in the TP1 and TP2 groups than in the control group.  Conclusion: The results of this study showed that T. parthenium caused a significant decrease in sperm chromatin quality, MDA level and germinal epithelium thickness at both doses. A reduction was found in the antioxidant enzyme level in the mice administrated with 50 and 100 mg/kg of T. parthenium.